Efficacy of pipeline embolization device vs. traditional coils in embolization of intracranial aneurysms: A systematic review and meta-analysis - Li, Wei; Xiao, Zaixing; Zhao, Kaixuan; Yang, Shijie; Zhang, Yichuan; Li, Bin; Zhou, Yu; Ma, Yong; Chai, Erqing (Frontiers in Neurology, 2022)
Introduction: The Pipeline embolization device (PED) has been increasingly used in intracranial aneurysm embolization, but there are conflicting findings as to whether its efficacy and safety are superior to those of traditional coils embolization (coils alone, stent-assisted coils, and balloon-assisted coils). The purpose of this meta-analysis was to evaluate the safety and efficacy of the Pipeline embolization device in intracranial aneurysm embolization by comparing with traditional coils.Methods: We systematically searched PubMed, Embase, Web of Science, and The Cochrane Library databases for randomized controlled trials and observational studies (case-control studies and cohort studies) comparing the efficacy of the Pipeline embolization device with traditional coils in intracranial aneurysm embolization published before April 1, 2022. The endpoints observed in this meta-analysis were procedure-related intracranial hemorrhage, procedure-related intracranial ischemia, other procedure-related complications (e.g., aneurysm rupture, neurological impairment, etc.), retreatment rate, complete occlusion (100%) of the aneurysm at the last follow-up , and favorable functional outcome (MRS ≤2).Results: A comprehensive analysis of the included literature showed that the PED group had a significantly better rate of complete aneurysm occlusion at the last follow-up (OR = 2.62, 95% Cl[1.94,3.55], p < 0.00001) and retreatment (OR = 0.20, 95% Cl[0.12,0.34], p < 0.00001) than the traditional coils group . However, in terms of procedure-related intracranial hemorrhage (OR=3.04, 95%Cl[1.08,8.57], p=0.04), other procedure-related complications (OR=2.91, 95%Cl[1.48,5.57], p=0.002), and favorable functional outcome of patients at the last follow-up (OR=0.4, 95%Cl[0.22,0.71], p = 0.002), the traditional coils group was superior to the PED group, while the difference between the two groups was not statistically significant in terms of procedure-related intracranial ischemic complications (OR=0.88, 95%Cl[0.47,1.64], p=0.68).Conclusion: PED had higher rates of complete aneurysm occlusion and lower rates of aneurysm retreatment compared with traditional coils, but traditional coils was superior to the PED group in terms of procedure-related intracranial hemorrhage complication and other procedure-related complications (aneurysm rupture, neurological impairment), and favorable functional outcome (mRS ≤2). This result still needs to be further confirmed by additional large-sample, multicenter, prospective randomized controlled trials.